Efficient photocatalytic carbon monoxide production from ammonia and carbon dioxide by the aid of artificial photosynthesis. Issue 8 (28th June 2017) - Huang, Zeai; Teramura, Kentaro; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro
Abstract : NH4 HCO3 was determined to be an effective electron donor for the photocatalytic conversion of CO2, whereby CO2 can be captured, stored, and efficiently converted into CO. Abstract : Ammonium bicarbonate (NH4 HCO3 ) was generated by the absorption of carbon dioxide (CO2 ) into an aqueous solution of ammonia (NH3 ). NH4 HCO3 was successfully used to achieve highly efficient photocatalytic conversion of CO2 to carbon monoxide (CO). NH3 and/or ammonium ions (NH4 + ) derived from NH4 HCO3 in aqueous solution were decomposed into nitrogen (N2 ) and hydrogen (H2 ). Stoichiometric amounts of the N2 oxidation product and the CO and H2 reduction products were generated when the photocatalytic reaction was carried out in aqueous NH4 HCO3 solution. NH3 and/or NH4 + functioned as electron donors in the photocatalytic conversion of CO2 to CO. A CO formation rate of 0.5 mmol h −1 was obtained using 500 mg of catalyst (approximately 7500 ppm) in ambient conditions (303 K, 101.3 kPa). Our results demonstrated that NH4 HCO3 is a novel inorganic sacrificial reagent, which can be used to increase the efficiency of photocatalytic CO production to achieve one step CO2 capture, storage and conversion.